2015
DOI: 10.1167/iovs.14-15299
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Intracellular Calcium Mobilization in IL-8 Activation in Human Retinal Pigment Epithelial Cells

Abstract: Collectively, our findings highlight the important role of intracellular calcium mobilization in the activation of IL-8. These findings may be helpful for the clinical applications in the age-related macular degeneration (AMD) prevention and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…In aged cells, disturbance of calcium homeostasis may lead to induced IL‐8 gene expression and IL‐8 secretion (Yang et al. ). Chronic oxidative stress has also been found to trigger the RPE cells to produce higher levels of IL‐8 stimulating both inflammation and angiogenesis, which, in turn, may lead to the development of CNV and exudative AMD (Zhu et al.…”
Section: Discussionmentioning
confidence: 99%
“…In aged cells, disturbance of calcium homeostasis may lead to induced IL‐8 gene expression and IL‐8 secretion (Yang et al. ). Chronic oxidative stress has also been found to trigger the RPE cells to produce higher levels of IL‐8 stimulating both inflammation and angiogenesis, which, in turn, may lead to the development of CNV and exudative AMD (Zhu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Complement activation products, C3a and C5a, are anaphylatoxins and mediate the expression of many inflammatory cytokines, including those associated with nuclear factor (NF)-κB pathway, a master switch for cytokine production 7 8. The NF-κB pathway mediates the expression of classic inflammatory cytokines (interleukin (IL)-6, IL-8) and those associated with the activation of the NLRP3 inflammasomes (IL-1β, IL-18), which play important roles in AMD pathology 9 10.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] Interleukin-8 is considered a potent chemo-attractant and activator of neutrophils and T-lymphocytes and is known to have both immune and vascular functions. 37 In the human eye, IL-8 was produced by retinal pigment epithelium and retinal microvascular endothelial cells 38,39 and was found elevated in the serum and aqueous of patients with active uveitis compared with non-active. 39 Researchers also reported that IL-8 is elevated in glaucoma eyes aqueous and is positively correlated with IOP and glaucoma damage.…”
Section: Discussionmentioning
confidence: 99%
“…37 In the human eye, IL-8 was produced by retinal pigment epithelium and retinal microvascular endothelial cells 38,39 and was found elevated in the serum and aqueous of patients with active uveitis compared with non-active. 39 Researchers also reported that IL-8 is elevated in glaucoma eyes aqueous and is positively correlated with IOP and glaucoma damage. 24,40 Another cytokine that was found elevated in post-vitrectomy eyes was IP-10.…”
Section: Discussionmentioning
confidence: 99%